2017
DOI: 10.1038/ncomms14756
|View full text |Cite
|
Sign up to set email alerts
|

Circulating tumour DNA reflects treatment response and clonal evolution in chronic lymphocytic leukaemia

Abstract: Several novel therapeutics are poised to change the natural history of chronic lymphocytic leukaemia (CLL) and the increasing use of these therapies has highlighted limitations of traditional disease monitoring methods. Here we demonstrate that circulating tumour DNA (ctDNA) is readily detectable in patients with CLL. Importantly, ctDNA does not simply mirror the genomic information contained within circulating malignant lymphocytes but instead parallels changes across different disease compartments following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
47
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(54 citation statements)
references
References 41 publications
4
47
0
3
Order By: Relevance
“…Current research has shown that ctDNA and CTC analysis can detect emerging mutations associated with treatment resistance, which includes the identification of T790M-EGFR mutations in NSCLC (Maheswaran et al 2008;Murtaza et al 2013;Oxnard et al 2014;Chabon et al 2016), KRAS mutations and mesenchymal-epithelial transition factor (MET) amplification in colorectal cancer patients receiving EGFR-based therapies (Diaz et al 2012;Misale et al 2012Misale et al , 2014Bardelli et al 2013;Siravegna et al 2015), the development of ESR1 mutations in hormone-resistant breast cancer (Yu et al 2014;Schiavon et al 2015), and the development of androgen receptor mutations and copy number changes, as well as the androgen receptor splice variant 7 (ARV7) in patients receiving treatment for advanced prostate cancer (Carreira et al 2014;Romanel et al 2015;Scher et al 2016). The application of serial ctDNA analysis through NGS of plasma DNA has also been shown to provide a comprehensive and unbiased assessment of genomic changes and tumor evolution during the acquisition of treatment resistance (Murtaza et al 2013(Murtaza et al , 2015Chabon et al 2016;Scherer et al 2016;Abbosh et al 2017;Yeh et al 2017b). Furthermore, the ability to isolate viable CTCs, culture CTCs ex vivo, and generate CTC-derived xenograft mouse models is opening up a vast array of new opportunities to perform drug sensitivity testing and study drug resistance mechanisms to guide personalized treatment approaches (Hodgkinson et al 2014;Yu et al 2014).…”
Section: Monitoring Tumor Burden and Therapeutic Responsesmentioning
confidence: 99%
“…Current research has shown that ctDNA and CTC analysis can detect emerging mutations associated with treatment resistance, which includes the identification of T790M-EGFR mutations in NSCLC (Maheswaran et al 2008;Murtaza et al 2013;Oxnard et al 2014;Chabon et al 2016), KRAS mutations and mesenchymal-epithelial transition factor (MET) amplification in colorectal cancer patients receiving EGFR-based therapies (Diaz et al 2012;Misale et al 2012Misale et al , 2014Bardelli et al 2013;Siravegna et al 2015), the development of ESR1 mutations in hormone-resistant breast cancer (Yu et al 2014;Schiavon et al 2015), and the development of androgen receptor mutations and copy number changes, as well as the androgen receptor splice variant 7 (ARV7) in patients receiving treatment for advanced prostate cancer (Carreira et al 2014;Romanel et al 2015;Scher et al 2016). The application of serial ctDNA analysis through NGS of plasma DNA has also been shown to provide a comprehensive and unbiased assessment of genomic changes and tumor evolution during the acquisition of treatment resistance (Murtaza et al 2013(Murtaza et al , 2015Chabon et al 2016;Scherer et al 2016;Abbosh et al 2017;Yeh et al 2017b). Furthermore, the ability to isolate viable CTCs, culture CTCs ex vivo, and generate CTC-derived xenograft mouse models is opening up a vast array of new opportunities to perform drug sensitivity testing and study drug resistance mechanisms to guide personalized treatment approaches (Hodgkinson et al 2014;Yu et al 2014).…”
Section: Monitoring Tumor Burden and Therapeutic Responsesmentioning
confidence: 99%
“…The effect of aromatase inhibitors on clonal architecture was shown by WGS analysis of matched tumour-normal pairs before and after neoadjuvant therapy in oestrogen-receptorpositive breast cancers, 49 and resistance and clonal advantage after therapy was identified in circulating tumour DNA in chronic lymphocytic leukaemia. 50 Here we showed for the first time that the analysis of subclonal events in matched metastatic tumour samples can also be used for a retrospective analysis of the timing metastatic events, even using standardcoverage WGS data, contributing to our understanding of the evolution of oligometastatic disease, as well as of the genomic imprint of chemotherapeutic treatments.…”
Section: Discussionmentioning
confidence: 94%
“…LN, bone marrow and PB) it represents an averaging tool and assesses the presence of these mutations across different biological sites. Yeh et al () demonstrated that monitoring ctDNA did not correlate with PB lymphocyte count, a traditional method of monitoring treatment response, as it is reflective of the dynamic of different disease compartments. However, they demonstrated a good correlation between ctDNA levels and MRD testing in CLL.…”
Section: Clinical Applications Of Next Generation Sequencingmentioning
confidence: 99%